ARTICULAR FEMORAL HEAD FRACTURE MANAGEMENT: A COMPREHENSIVE SYSTEMATIC REVIEW - Rapmartua Ompusunggu, Indra Hadi; Yulanda Putra, Yosie; Auliya, Ahsan (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2024)
Background: Femoral head fractures (FHFs) are relatively rare injuries usually caused by high-energy trauma. They typically occur after a posterior dislocation, and approximately 5 to 15 of posterior hip dislocations involve FHFs. FHFs may also occur simultaneously with acetabular fractures, with an estimated incidence of 29.2 In addition, the incidence of ipsilateral femoral head and neck fractures (iFHNF) is low. However, iFHNFs, as a special type of fracture, have the worst prognosis among all FHFs The aim: The aim of this study to show about articular femoral head fracture management. Methods: By comparing itself to the standards set by the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) 2020, this study was able to show that it met all of the requirements. So, the experts were able to make sure that the study was as up-to-date as it was possible to be. For this search approach, publications that came out between 2014 and 2024 were taken into account. Several different online reference sources, like Pubmed and SagePub, were used to do this. It was decided not to take into account review pieces, works that had already been published, or works that were only half done. Result: In the PubMed database, the results of our search get 17 articles, whereas the results of our search on SagePub get 489 articles, on Google Scholar 8050 articles. Records remove before screening are 5860, so we get 2696 articles fos screening. After we screened based on record exclude, we compiled a total of 12 papers. We included five research that met the criteria. Conclusion: Open reduction and internal fixation of femoral head fracture using surgical hip dislocation through Ganz approach is a viable treatment option and provides satisfactory results with low complication rates.